2021
DOI: 10.1002/pra2.505
|View full text |Cite
|
Sign up to set email alerts
|

What's Next for Information World Mapping?: International and Multidisciplinary Uses of the Method

Abstract: As use of arts-involved and data visualization methods increases in information science, it is important to reflect on strengths and weaknesses of various methods. In this 90-minute panel, an international lineup of information researchers will share their experiences using the participatory, visual elicitation technique information world mapping (IWM) in their work. Panelists will discuss ways to adapt the technique to different contexts, share their thoughts on what is next for IWM, and raise questions regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…These major findings contribute to the IWM literature by identifying and further describing additional advantages of using the method beyond those initially identified by Greyson et al ( , 2021. The authors' various applications of IWM also identified several potential challenges.…”
Section: Discussion: Major Findings Challenges and Recommendations Fo...mentioning
confidence: 64%
See 4 more Smart Citations
“…These major findings contribute to the IWM literature by identifying and further describing additional advantages of using the method beyond those initially identified by Greyson et al ( , 2021. The authors' various applications of IWM also identified several potential challenges.…”
Section: Discussion: Major Findings Challenges and Recommendations Fo...mentioning
confidence: 64%
“…Mabi observed that ceding control meant accommodating participants' (generally women's) multitasking, as they performed culturally expected roles in the home such as childcare. Seeing this multitasking occur added additional context to the research, enriching the data collected (Greyson et al, 2021).…”
Section: Discussion: Major Findings Challenges and Recommendations Fo...mentioning
confidence: 99%
See 3 more Smart Citations